COVID-19 lockdown: Online survey of psychosocial factors of adolescents - Deoshree Akhouri (Wolters Kluwer Medknow Publications, 2021)
Background: The coronavirus pandemic has affected more than 14 million people in the world. Adults are somehow able to manage their stress created by the most fearful disease. However, it is the children and adolescents who are most affected by COVID-19 lockdown. Aim: This study aimed to assess the effect of COVID-19 lockdown on adolescent's psychosocial factors. Materials and Methods: Using the Google Form link, a questionnaire was developed and an online survey was conducted. This online questionnaire consisted of 40 items assessing personal, social, academic, and family domains related to adolescents. Results: A total of 223 responses were obtained. The results indicate that 6.5% of adolescents experience extreme level of anxiousness, 29.8% become little irritable and angry, affecting their personal/emotional domain. About 12.6% of the adolescents are uncomfortable with social distancing and 48.4% of them greatly miss their friends; 38.1% miss their school and 28.8% are unable to clear their doubts through online teaching. Mathematics was the most uncomfortable subject for them to deal with 49.8%. About 79% of adolescents suffer mildly from family distress, 43.3% (extremely) are eagerly waiting for the lockdown to end. Conclusion: Among all four domains, the family domain was the most affected due to COVID-19 lockdown, followed by social, academic, and personal domains.